PRODUCTION OF ginger vinegar - Leonel,Magali (2015)
Vinegar is a food of condiments group that have great use in the food industry. This study aimed to evaluate the effects of parameters of the acetic fermentation process in the production of ginger vinegar. A suspension of ginger rhizomes with 12% of starch was subjected to enzymatic hydrolysis process to obtain hydrolyzed with 85.6% of glucose. After the alcoholic fermentation the wine was obtained with 40.3% ethanol. The acetic fermentation process of ginger alcoholic solution followed a completely randomized design in a factorial for three factors at two levels. The independent variables were: temperature, nutrients and proportion of "strong vinegar" and alcoholic solution (initial acidity). Results showed variation from 2.74 to 3.70% for dry extract and 2.13 to 2.83 % for ash in vinegars. The profile of organic acids of ginger vinegars showed the presence of acetic, citric, malic and succinic acids in all treatments. The condition of 20°C, initial acidity 1:1,with addition of nutrients allow obtaining good quality vinegars and higher GK yields